Retrospective analysis of 5 year survival and prognostic factors of breast cancer patients treated in HUSM - Krishnan, Yogessvaran (2020)
Breast cancer is the most prevalent malignancy and is one of the leading cause of cancer related mortality and the prevalence is in the increasing trend in Malaysia. The prognosis of breast cancer is better than other malignancies, hence identifying prognostic factors in patients suffering from breast cancer plays a significant role in management. This study aims to determine 5 year survival rate of breast cancer patients and to study the effects of prognostic factors in affecting the survival of breast cancer in HUSM. This is a retrospective study conducted at Hospital Universiti Sains Malaysia (HUSM). A total of 172 patients with clinically and histologically confirmed diagnosis of breast cancer from January 2009 until December 2013 were included in the study and all patients were followed up for five years from the time of diagnosis. Patients' sociodemographic and clinical information was collected to determine the prognostic factors. Survival analysis was done using the Kaplan-Meier method, while the prognostic factors of survival were determined using the Cox regression analysis. The mean survival time for overall death were 47.4 months and the mean survival time for breast cancer related death were 48.6 months. The results showed that hazards for breast cancer related death increased as the tumour size increases. . Patients with T2 tumour size has 9.7 times higher hazards [HR (95% CI): 9.64 (1.97, 47.53), p = 0.005], T3 has 5.6 times higher hazards [HR (95%CI): 5.56 (1.10, 28.04), p = 0.038] and T4 has 24.5 times more hazards [HR (95%CI): 24.49 (5.42, 110.65), p<0.001] for breast cancer death compared to T1. Patients with positive Cerb B2 status were found to have 10 times higher hazards for breast cancer compared to negative Cerb B2 status [HR (95%CI): 10.43 (4.49, 24.26), p<0.001]. Hormonal therapy seems to be protective towards breast cancer death as these patients had 94% lower hazards for breast cancer death compared to patients with other treatment methods [HR (95%CI): 0.061 (0.024, 0.151), p<0.001] In conclusion, the mean survival time for breast cancer patients in HUSM was 48.6 months, which was low as compared to other centres. The significant prognostic factors identified were the tumor size, expression of Cerb B2, hormonal therapy and late stage of disease. Hence it is essential to create better awareness of breast cancer to implement a good prevention and control programme